THE INFLUENCE OF SERVICE QUALITY ON PATIENT LOYALTY THROUGH SATISFACTION AS AN INTERVENING VARIABLE - Imelda Thein; Yesus Armiro Korbaffo; Marlinda Pala Bani (Sean Institute, 2023)
This study aims to determine and explain: the effect of service quality on patient loyalty through satisfaction as an intervening variable. The data used in this study are primary data obtained through questionnaires distributed to 60 respondents. The data analysis technique used is descriptive analysis and inferential analysis. The inferential analysis tool is Path Analysis with the help of SPSS 20.0 software. The results of this study is the analysis of service quality has a significant effect on satisfaction and service quality has a significant effect on patient loyalty and service quality has a significant effect on patient loyalty which is mediated by patient satisfaction.